2003
DOI: 10.1007/s11920-003-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for mood and anxiety disorders: Quetiapine and aripiprazole

Abstract: Atypical antipsychotic agents have a broad range of therapeutic efficacy, a relatively low incidence of causing extrapyramidal adverse effects, and a low tardive dyskinesia profile. This has led to very rapid growth in the use of these compounds as broad-spectrum psychotropic agents, and it has been reported that more than 70% of prescriptions for atypical antipsychotic medications are being used for conditions other than schizophrenia. In the area of bipolar disorder, in particular, atypical antipsychotic age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…While reductions in the YMRS were similar for the two groups, continuation rates with aripiprazole were significantly higher when compared with haloperidol (50.9 vs. 29.1%). In both studies, data indicated higher levels of compliance in patients randomized to aripiprazole; these findings are important given the high rate of medication noncompliance in patients with bipolar disorder (75). These results indicate that aripiprazole is effective as a single agent in acute mania with an efficacy similar to that of haloperidol at a flexible but moderately high dose.…”
Section: Mood Disordersmentioning
confidence: 73%
“…While reductions in the YMRS were similar for the two groups, continuation rates with aripiprazole were significantly higher when compared with haloperidol (50.9 vs. 29.1%). In both studies, data indicated higher levels of compliance in patients randomized to aripiprazole; these findings are important given the high rate of medication noncompliance in patients with bipolar disorder (75). These results indicate that aripiprazole is effective as a single agent in acute mania with an efficacy similar to that of haloperidol at a flexible but moderately high dose.…”
Section: Mood Disordersmentioning
confidence: 73%
“…All patients completed their outpatient therapy in agreement with the physician in a stable state. We treated only alcohol dependent patients with quetiapine as relapse prevention after withdrawal, who showed at least one of the following target symptoms: persisting craving [2], persisting sleep disorder [4], persisting excitement [5], persisting depressive symptoms [22] or persisting anxiety symptoms [23], for details see Table 1. After at least one week of abstinence we started quetiapine with 100 mg/day in the evening.…”
Section: Subjectsmentioning
confidence: 99%
“…Dopamine release is controlled by a negative feedback of dopamine on presynaptic D 2 dopamine autoreceptors. Under conditions of basal dopamine excess, aripiprazole acts as an agonist at the presynaptic autoreceptor to decrease dopamine synthesis and release (5). The resultant decrease in presynaptic dopamine release augments the antagonist activity of aripiprazole at postsynaptic D 2 receptors in the mesolimbic pathway where dopamine excess is believed to be responsible for psychotic symptoms.…”
Section: Mechanism Of Actionmentioning
confidence: 99%